Neonatal seizures: Is there a relationship between ictal electroclinical features and etiology? A critical appraisal based on a systematic literature review. Issue 1 (25th January 2019) - Nunes, Magda L.; Yozawitz, Elissa G.; Zuberi, Sameer; Mizrahi, Eli M.; Cilio, Maria Roberta; Moshé, Solomon L.; Plouin, Perrine; Vanhatalo, Sampsa; Pressler, Ronit M.
Summary: The aim of this study was to evaluate whether specific etiologies of neonatal seizures have distinct ictal electroclinical features. A systematic review of English articles using the PubMed database since 2004 (last update 9/26/16). Search terms included text words and Medical Subject Headings (MeSH) terms related to neonatal seizures. Eligible articles included reports of neonates with seizures with a full description of seizure semiology and electroclinical findings. Independent extraction of data was performed by 2 authors using predefined data fields, including study quality indicators. Data were collected for every individual patient described in the articles. The dataset was analyzed with the Fisher exact test. The initial search led to 8507 titles; using filters, 2910 titles and abstracts were identified, with 177 full texts selected to be read. Fifty‐seven studies were included in the analysis with 151 neonates (37.7 male and 62.9% term). Genetic etiologies (51%) and sequential seizures (41.1%) predominated in this sample and hypoxic‐ischemic encephalopathy (HIE) accounted for only 4%. The low prevalence of HIE observed was probably due to a publication bias. A significant association was found between etiology and seizure type: hemorrhage with autonomic seizures ( P  = 0.003), central nervous system (CNS) infection and stroke with clonic seizures ( P  = 0.042, P  < 0.001, respectively), metabolic/vitamin‐related disorders, and inborn errors of metabolism with myoclonic seizures ( P  < 0.001). There were also specific electroencephalography (EEG) patterns seen with certain etiologies: vascular disorders and electrolyte imbalance with focal ictal discharges ( P  < 0.001, P  = 0.049 respectively), vitamin‐related disorders with multifocal ( P  = 0.003), and all categories of genetic disorders with burst‐suppression ( P  < 0.001). Clonic and autonomic seizures were more frequently present with focal EEG abnormalities ( P  = 0.001 and P  < 0.001), whereas tonic and myoclonic seizures present with burst‐suppression ( P  = 0.001, P  = 0.005). In conclusion, our data suggest that specific associations of etiologies of neonatal seizures with distinct clinical features and EEG patterns might help in the decision to establish appropriate treatment.